Fracture characteristics of PEEK at various stress triaxialities - Chen, Fei; Gatea, Shakir; Ou, Hengan; Lu, Bin; Long, Hu (Elsevier, 2016)
Polyether-ether-ketone (PEEK) is an alternative to metal alloys in orthopaedic applications. It gives significant advantages including excellent mechanical properties and non-toxicity. In this work, a set of specimens with different notched radii were selected to examine the effect of triaxial state of stress on the fracture behavior of PEEK. Fractographic analysis via scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) further elucidated the fracture micromechanisms. Distinct fracture patterns were identified under different stress triaxialities. In addition, the microstructural inclusion properties in PEEK specimen such as inclusion size and chemical composition were analysed and determined. Finite element simulations were carried out to evaluate the correlation of observed fracture characteristics with different stress triaxialities.